2017
DOI: 10.1088/1475-7516/2017/05/031
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the dark sector interaction with LISA

Abstract: We perform a forecast analysis of the ability of the LISA space-based interferometer to reconstruct the dark sector interaction using gravitational wave standard sirens at high redshift. We employ Gaussian process methods to reconstruct the distance-redshift relation in a model independent way. We adopt simulated catalogues of standard sirens given by merging massive black hole binaries visible by LISA, with an electromagnetic counterpart detectable by future telescopes. The catalogues are constructed consider… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 86 publications
1
72
0
Order By: Relevance
“…The cosmic isotropy can be ruled out at 3σ C.L. and the dipole direction can be constrained roughly around 20% at 2σ C.L., as long as the dipole amplitude is larger than 0.03, 0.06 and 0.025 for MBHB models Q3d, pop III and Q3nod with increasing constraining ability, respectively, which is consistent with the results from [53].…”
Section: Summary Of Resultssupporting
confidence: 87%
“…The cosmic isotropy can be ruled out at 3σ C.L. and the dipole direction can be constrained roughly around 20% at 2σ C.L., as long as the dipole amplitude is larger than 0.03, 0.06 and 0.025 for MBHB models Q3d, pop III and Q3nod with increasing constraining ability, respectively, which is consistent with the results from [53].…”
Section: Summary Of Resultssupporting
confidence: 87%
“…It has been found that the presence of an interaction in the dark sector could successfully reconcile the long lasting cosmic coincidence problem [3,4,5,6,7]. Following this, a number of investigations in the context of interacting DE -DM models were performed by many investigators [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43] (also see two review articles in this direction [44,45]). An interesting outcome from the interaction is that, it could naturally explain the phantom dark energy equation-ofstate [46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…This can be done using the technique of gaussian processes, that allows the reconstruction of a function directly from the data. Several applications of gaussian processes in cosmology have been discussed in [179,[218][219][220][221][222][223][224][225][226]. In [204] this technique has been applied to the reconstruction of d gw L (z)/d em L (z).…”
Section: The Advanced Ligo/virgo/kagra Networkmentioning
confidence: 99%